PRAKTIK ZAKAT IKAN BANDENG HASIL TAMBAK DI DESA RANDUBOTO - Cholifatul Aisah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
The average farmer village pond Randuboto issued their zakat directly in the form of fish itself. Regarding the time is different, there is every harvest and every year there is also the time of the harvest has reached one ton or more. The amount of zakat distributed generally lumped in each family and all the neighbors around the home are entitled to zakat the milkfish, without distinguishing between capable and incapable. Practice division milkfish harvest is not charity, but charity, although intended as a charity because it is not in accordance with the provisions of zakat in Islam, which does not use the calculation nisab and haul in the determination of zakat. In addition, the fish harvest is not only given to the eight groups which by syara’ has been defined as mustahik zakat, but evenly distributed to neighbors and close relatives regardless capable or not capable economically.